Potential design parameters for enhancing thermal comfort in tropical terrace house: a case study in Kuala Lumpur - Sadafi, Nasibeh; Salleh, Elias; Lim, Chin Haw; Jaafar, Mohd Fakri Zaky (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
Thermal comfort conditions in residential buildings vary according to the designs, modifications of the house and adaptation of the occupants. While air-conditioning is the most popular form of adaptation, natural ventilation is still relied upon for some parts. This study investigates thermal comfort performance of terrace housing in Kuala Lumpur, Malaysia, using Fanger’s predicted mean vote (PMV) thermal comfort index. A case study of a terrace house was carried out in a housing scheme in Kuala Lumpur where field measurement was conducted during a three-day recording in naturallyventilated space of the house. The study showed that the house was thermally comfortable for almost fifteen hours during day and night. Comfort conditions mostly occurred during night hours while around noon hours could be considered as critical times. To improve the thermal conditions, ceiling fans were used to increase the indoor air velocity. However, it was observed that this measure did not improve the thermal comfort condition when the air temperature had reached its maximum level. On the other hand, reducing the solar heat gain could improve the thermal comfort condition of the house.